Specialty preferences among Nigerian medical students: a cross sectional study - Tobi Olajide; Chioma Ezebialu; Christabel Uche-Orji; Ridwanullah Abdullateef; Chisom Okoye; Esther Olaoye; Jolly Thomas; Joy Adeniyi; Angel Ogiemudia; Simon Aina; Oluwatimilehin Oladapo; Emmanuel Ibitunde; et al. (BMC Medical Education)
Abstract Introduction Specialty preferences among medical students significantly influence healthcare workforce distribution and equity. Nigeria, with its low physician-to-patient ratio, faces critical challenges in addressing healthcare demands. Understanding the specialty preferences of medical students and the factors influencing these choices is essential for workforce planning. This study aimed to investigate these preferences among Nigerian medical students and the implications for healthcare planning. Methods A cross-sectional study was conducted using convenience sampling among 439 penultimate and final-year medical students across fully accredited Nigerian medical schools between July and October 2024. Data were collected using an online self-administered questionnaire, which included socio-demographics, specialty preferences, and influencing factors. Analysis was performed using the Statistical Product and Service Solutions (SPSS) version 27. Descriptive and inferential statistics were used to summarize categorical variables as frequencies and proportions, while continuous variables were reported as means and standard deviations. Ethical approval was obtained from the University of Ibadan/University College Hospital (UI/UCH) Health Research Ethics Committee. Results The mean age of participants was 23.62 ± 2.95 years, with 53.1% male and 45.3% female. Most students were in their penultimate year (60.1%). Obstetrics and Gynecology was the most preferred first-choice specialty (14.7%), followed by Cardiothoracic Surgery (11.8%). A significant proportion of students were undecided (13.3%) about their first choice. Diagnostic specialties like Radiology and Pathology had the least interest (< 1%). Significant factors influencing specialty choice included personal interest (87%), content of specialty (85.3%), and potential lucrativeness (77%). Statistically significant associations were observed for potentially lucrativeness (p < 0.001), the desired practice setting (p = 0.004), shorter training periods (p < 0.001), minimal or predictable work hours (p < 0.001), age (p = 0.003), and academic level (p = 0.034). Conclusion This study explored specialty preferences among Nigerian medical students revealing a strong inclination toward Obstetrics and Gynecology, Surgery, and Internal Medicine. Career choices were influenced by factors such as personal interest, prestige, intellectual challenge, income, academic level, and gender. The study revealed the need for structured career counseling and increased exposure to underrepresented specialties to address the uneven distribution of specialists in Nigeria. Tailored mentorship programs, improved financial incentives, and enhanced training opportunities are critical for optimizing the healthcare workforce and achieving equity.